2016
DOI: 10.1371/journal.pone.0162024
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Fgf21 Expression Is Repressed after Simvastatin Treatment in Mice

Abstract: Fibroblast growth factor 21 (Fgf21) is a hormone with emerging beneficial roles in glucose and lipid homeostasis. The interest in Fgf21 as a potential antidiabetic drug and the factors that regulate its production and secretion is growing. Statins are the most widely prescribed drug for the treatment of dyslipidemia. However, the function of statins is not limited to the lowering of cholesterol as they are associated with pleiotropic actions such as antioxidant, anti-inflammatory and cytoprotective effects. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
(80 reference statements)
1
6
0
Order By: Relevance
“…A recent meta-analysis of controlled clinical trials has shown reduction of plasma free fatty acids (FFAs) by atorvastatin [33], and FFAs can stimulate FGF21 expression in vitro [34]. Short-term simvastatin suppresses hepatic FGF21 expression and reduces circulating FGF21 levels in mice as well as FGF21 expression in mouse primary hepatocytes [10]. All these findings are consistent with our clinical study results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A recent meta-analysis of controlled clinical trials has shown reduction of plasma free fatty acids (FFAs) by atorvastatin [33], and FFAs can stimulate FGF21 expression in vitro [34]. Short-term simvastatin suppresses hepatic FGF21 expression and reduces circulating FGF21 levels in mice as well as FGF21 expression in mouse primary hepatocytes [10]. All these findings are consistent with our clinical study results.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is unknown whether circulating FGF21 levels can predict CVD events in statin-treated patients. This is particularly important given that statins are widely used for CVD prevention, and hepatic FGF21 expression is repressed in statin-treated mice [10].…”
Section: Introductionmentioning
confidence: 99%
“…p for interaction was estimated by including the interaction term in the regression models in the full sample after adjustment for the main effects of the covariates. Moreover, as FGF21 levels have been reported to be affected by lipid-lowering medications [10,20] and lipid-lowering medication also affect triglycerides and HDL-C, we excluded participants on lipid-lowering medications at baseline in a sensitivity analysis. A two-tailed p < 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…10 FGF21 specifically regulates glucose uptake in adipocytes, improves insulin resistance, protects islet beta cells, lowers blood lipid levels, and reduces other lipid metabolism functions in diabetes, indicating that it has great potential as a clinical treatment for metabolic syndromes, such as diabetes, obesity, atherosclerosis, and hepatic adipose infiltration, among other conditions. [11][12][13][14][15][16][17] FGF21 protein is expressed at high levels in the liver, particularly in the fasted state, and causes a series of glycolipid metabolic reactions. [18][19][20][21] In addition, FGF21 is the only FGF member that has not been shown to promote mitosis, which may reduce the risk of side effects in clinical treatments.…”
Section: Introduction Type 2 Diabetes Mellitus (T2dmmentioning
confidence: 99%